Active linewidth-narrowing of a mid-infrared quantum cascade laser without optical reference - Tombez, Lionel; Schilt, Stephane; Hofstetter, Daniel; Südmeyer, Thomas (My University, 2013)
We report on a technique for frequency noise reduction and linewidth-narrowing of a distributed-feedback mid-IR quantum cascade laser (QCL) that does not involve any optical frequency reference. The voltage fluctuations across the QCL are sensed, amplified and fed back to the temperature of the QCL at a fast rate using a near-IR laser illuminating the top of the QCL chip. A locking bandwidth of 300 kHz and a reduction of the frequency noise power spectral density by a factor of 10 with respect to the free-running laser are achieved. From 2 MHz for the free-running QCL, the linewidth is narrowed below 700 kHz (10 ms observation time).